If
![\frac{2 + \sqrt{5} }{2 - \sqrt{5} } = x \frac{2 + \sqrt{5} }{2 - \sqrt{5} } = x](https://tex.z-dn.net/?f=+%5Cfrac%7B2+%2B++%5Csqrt%7B5%7D+%7D%7B2+-++%5Csqrt%7B5%7D+%7D++%3D+x)
and
![\frac{2 - \sqrt{5} }{2 + \sqrt{5} } = \: y \frac{2 - \sqrt{5} }{2 + \sqrt{5} } = \: y](https://tex.z-dn.net/?f=+%5Cfrac%7B2+-++%5Csqrt%7B5%7D+%7D%7B2+%2B++%5Csqrt%7B5%7D+%7D++%3D++%5C%3A+y)
find the value of
![{x}^{2} - {y}^{2} {x}^{2} - {y}^{2}](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++-++%7By%7D%5E%7B2%7D+)
Answers
Answered by
2
Similar questions